Unique Electrochemiluminescence Behavior of 4-Chromanone and Chromone and their Sensing Application. Issue 6 (6th April 2020) - Qiu, Xia; Qing, Xiang; Sufan, Wang; Zhu, Yinggui
Abstract : 4-Chromanone and chromone, these two structurally similar pharmaceutical intermediates play a vital role in drug synthesis, but their related electrochemical properties have not been reported. In this work, we have found that 4-chromanone and chromone can generate strong electrochemiluminescence (ECL) during their reduction by using K2 S2 O8 as co-reactant in H3 BO3 -Na2 B4 O7 buffer solution. The ECL reaction mechanism has been investigated carefully by studying their fluorescence (FL) spectrum, ECL spectrum, and the important role of co-reactants in the system. Moreover, it has been found that iodide ion (I − ) can inhibit the ECL signal of 4-chromanone and the ECL decrease degree is related to the amount of added I − . Therefore, a new ECL method for the detection of iodide ion has been established with high sensitivity, good selectivity and wide linear range, which can be used for detecting I − in real samples.